Design of an ASTM E119 fire environment in a large compartment - Zhang, Chao (Fire Technol, 2019)
Structural fire protection design in the United States is based on prescriptive fire-resistance ratings of individual load-bearing elements which are derived from standard fire testing, e.g. ASTM E119. In standard fire testing, a custom-built gas furnace is traditionally used to heat a test specimen by following the gas temperature-time curve prescribed in the ASTM E119 standard. The span length of the test specimen seldom exceeds 6 m due to the size limitations of available furnaces. Further, the test specimen does not incorporate realistic structural continuity. This paper presents a basis for designing an ASTM E119 fire environment in a large compartment of about 10 m wide, 7 m deep and 3.8 m high constructed in the National Fire Research Laboratory of the National Institute of Standards and Technology. Using the designed fire parameters, a full-scale experiment was carried out on December 20, 2018. The measured average upper layer gas temperature curve was consistent with the E119 fire curve. The maximum difference between the measured curve and the E119 fire curve towards the end of the test was about 70 °C (7%). The study indicates that by proper design and control, the time-temperature curve for the standard fire testing may be approximated in a real compartment. The experimental method suggested in this paper would allow to extend the application of the standard fire testing to large-scale structures not limited by the size of furnaces, to experimentally evaluate the thermally-induced failure mechanism of structural systems including connections and frames, and to advance fire protection design methods.